2007
DOI: 10.1016/j.devcel.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A Multipotent Progenitor Domain Guides Pancreatic Organogenesis

Abstract: The mammalian pancreas is constructed during embryogenesis by multipotent progenitors, the identity and function of which remain poorly understood. We performed genome-wide transcription factor expression analysis of the developing pancreas to identify gene expression domains that may represent distinct progenitor cell populations. Five discrete domains were discovered. Genetic lineage-tracing experiments demonstrate that one specific domain, located at the tip of the branching pancreatic tree, contains multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
596
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 481 publications
(639 citation statements)
references
References 46 publications
34
596
0
5
Order By: Relevance
“…The tip cells retain expression of the ''primary multipotency markers'' Pdx1 and Ptf1a, and have the molecular signature of Pdx1 þ Ptf1a þ CpaI þ cMyc HI . Genetic lineage tracing studies performed using CpaI-CreER (here the enzyme gene Cpa1 could be considered a surrogate for Ptf1a, because Ptf1a regulates its expression) showed that tip cells at E12.5 produce all pancreatic cell types (endocrine, duct, acini), confirming their MPC nature (Zhou et al, 2007).…”
Section: Branching Mechanisms and Progenitor Domain Compartmentalizationmentioning
confidence: 88%
See 4 more Smart Citations
“…The tip cells retain expression of the ''primary multipotency markers'' Pdx1 and Ptf1a, and have the molecular signature of Pdx1 þ Ptf1a þ CpaI þ cMyc HI . Genetic lineage tracing studies performed using CpaI-CreER (here the enzyme gene Cpa1 could be considered a surrogate for Ptf1a, because Ptf1a regulates its expression) showed that tip cells at E12.5 produce all pancreatic cell types (endocrine, duct, acini), confirming their MPC nature (Zhou et al, 2007).…”
Section: Branching Mechanisms and Progenitor Domain Compartmentalizationmentioning
confidence: 88%
“…For example, how the simplified tip-trunk model (Zhou et al, 2007; Fig. 2A) fits into this emerging structure might require a large-scale, detailed 3-dimensional mapping effort, paying specific attention to the stage of pancreas development, and the general and precise geographic location within the expanding epithelial arbor.…”
Section: Branching Mechanisms and Progenitor Domain Compartmentalizationmentioning
confidence: 99%
See 3 more Smart Citations